BIRTH WEIGHT : A COMMUNITY PERSPECTIVE - SRIVASTAVA, J P (Indian Journal of Community Health, 2003)
India has a dubious distinction of belonging to the top bracket of countries with a very high under-5 Mortality Rate (U5MR) of above 96/1000 live births. The U5MR considered the single most significant basic indicator of health status of a community, is proportional to the Infant Mortality Rate (IMR) which in turn is contributed to directly and indirectly by the incidence of low Birth Weight (LB W).About 25 million LB W are born each year consisting 17% of all live births,nearly 95% of them in developing countries. About 26% of newborns are LBW in India, and indeed over 16% in those countries with very high U5MR.Both preterm and small-for-dates almost equally make up this category of vulnerable infants predisposed to asphyxia, feeding problems, anemia and growth failure. Considering the close relationship of birth weight with perinatal and infant morbidity as well as mortality, it is crucial to identify the liigh risk groups of low birth weight babies as early as possible.Unfortunately, in a community where 80% of newborns never get to have their weight measured, this itself is a tall order. In our society, the cry of the newborn is greeted with anxious queries about the sex of the baby and not his wellbeing and potential for healthy survival. The basic concept of the importance of birth weight is missing even among educated families. Indeed, it is as if the weighing machine has no place in the requirements at childbirth. In the absence of this basic facility, field workers and TBAs must report to other means to identify babies at risk. Mid-arm circumference, thigh circumference, foot length, and skin-fold thickness etc. are measurements that have been correlated satisfactorily with the baby’s weight. Simple tools like coloured strips have been developed and these show promise of applicability in field situation for identification of LB W by TBAs for early referral.